2008
DOI: 10.1103/physrevlett.100.203002
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Emission Spectra of Fluorescent Molecules with Single Plasmonic Nanoresonators

Abstract: We show that plasmonic nanoresonators composed of two gold nanoparticles change not only the intensity but also the spectral shape of the emission of fluorescent molecules. The plasmonic resonance frequency can be tuned by varying the distance between the nanoparticles, which allows us to selectively favor transitions of a fluorescent molecule to a specific vibrational ground state. Experimental data from correlated scattering and fluorescence microscopy agree well with calculations in the framework of general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
460
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(477 citation statements)
references
References 29 publications
13
460
1
3
Order By: Relevance
“…In general, the total PLE may be factored into its con- tributions from the pump and emission energies [4,10]. We have verified that the influence of resonant pump enhancements is negligible by exciting the sample with different k-vectors and/or polarizations.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In general, the total PLE may be factored into its con- tributions from the pump and emission energies [4,10]. We have verified that the influence of resonant pump enhancements is negligible by exciting the sample with different k-vectors and/or polarizations.…”
mentioning
confidence: 87%
“…Coupled semiconductor nanocrystal quantum emitters and metallic nanostructures offer an ideal platform for this purpose [1][2][3]: the emission energy can be tuned by varying the nanocrystal size due to quantum confinement of charge carriers, while the emitted light can be enhanced and controlled by structuring the metal to sustain surface plasmon polaritons which are resonant with the emission. It has been shown that Localized Surface Plasmon Resonances (LSPRs) in metallic nanoparticles may lead to a strong confinement of optical radiation into subwavelength volumes, resulting in a drastic modification of the emission spectra [4], and radiative decay rates [5], of emitters in this volume. However, such strong effects depend on an accurate positioning of the emitter in the region where the large electromagnetic enhancements occur.…”
mentioning
confidence: 99%
“…Linear molecular spectroscopies such as Raman and fluorescence have found their plasmonenhanced analogs in surface-enhanced Raman scattering (SERS) and surface-enhanced fluorescence; both are now routinely realized in the extreme limit of singlemolecule detection; see, e.g., Refs. [7,8,9,10]. And plasmon-enhanced versions of n-wave mixing and hyperRaman scattering [11,12], as well as other nonlinear spectroscopies, are rapidly being explored as ultrasensitive probes of molecular structure complementary to those linear.…”
mentioning
confidence: 99%
“…Strongly coupled plasmonic nanostructures are particularly well suited to build biosensor-and spectroscopy devices as they have been shown to enhance Raman scattering and uorescence intensity and also shape the emission spectrum of single molecules that are positioned in the nanoantenna gap. [144][145][146] Nanoparticles optically trapped in a liquid at room temperature are subject to signicant Brownian motion. This motion is damped to a certain level by the strong gradient forces induced by the trapping laser.…”
Section: Manipulation Of Biomimetic and Biological Systemsmentioning
confidence: 99%